WAYS TO PREVENT THE NEGATIVE SOCIO-PSYCHOLOGICAL IMPACT OF MISLEADING INFORMATION - Avetisyan, Armen (Modern Psychology, 2023)
In the article, we presented ways to prevent the negative socio-psychological impact of misleading information on a person, a group. We discussed the forms of spreading misleading information via the Internet, the possible negative consequences of their impact on humans, and various social groups. In particular, we presented two main strategies for preventing the destructive socio-psychological impact of misleading information on student youth, emphasizing the role of professional educational programs in the process of studying at the university: the final results that ensure the socio-psychological security of the individual in the specifications, the availability of appropriate courses that ensure their achievement in the curricula.